Elevated HSP90 associates with expression of HIF‐1α and p‐AKT and is predictive of poor prognosis in nasopharyngeal carcinoma. Issue 2 (17th June 2019) - Feng, Juan; Xie, Guiyuan; Zhan, Yuting; Lu, Junmi; Xu, Lina; Fan, Songqing; Wang, Weiyuan
Abstract : Aims: HSP90, as a molecular chaperone, has numerous substrate proteins, including HIF‐1α and p‐AKT, but the relationships among HSP90, HIF‐1α and p‐AKT have not been investigated in NPC. We examined and analysed the correlation between expression of HSP90, HIF‐1α and p‐AKT and clinicopathological features of NPC. Methods: We collected 445 cases of NPC and 54 cases of non‐cancerous nasopharyngeal epithelia tissues, detected expression of HSP90, HIF‐1α and p‐AKT proteins in these tissues by immunohistochemistry. Results: The results indicated that overexpression of HSP90, HIF‐1α and p‐AKT in NPC was significantly higher than that in non‐cancerous nasopharyngeal epithelia ( P  < 0.05). The overexpression of HIF‐1α in primary NPC was significantly lower than that in matched lymph node metastatic NPC ( P  = 0.024) or recurrent NPC ( P  = 0.039). The overexpression of HSP90 ( P  < 0.001) and HIF‐1α ( P  = 0.031) was evidently higher in late stage NPC. NPC patients with lymph node metastasis (LNM) had a higher overexpression rate of HSP90 ( P  < 0.001) than those without LNM. Increased HSP90 expression was positively associated with HIF‐1α expression ( r  = 0.367, P  < 0.001) and p‐AKT ( r  = 0.142, P  = 0.003) expression in NPC. Furthermore, HIF‐1α was also related to p‐AKT expression ( r  = 0.114, P  = 0.017). The overall survival rate for NPC patients with up‐regulated HSP90 was significantly lower than those with down‐regulated HSP90 ( P  < 0.001), as was found with raised HIF‐1α ( P  = 0.036) and increased p‐AKT ( P  = 0.044). Multivariate Cox regression analysis further identified that HSP90 and HIF‐1α were independent poor prognostic factors for NPC. Conclusions: Taken together, elevated HSP90 was associated with expression of HIF‐1α and p‐AKT in NPC. Furthermore, high expression of HSP90 and HIF‐1α could be used as a novel independent poor prognostic biomarker for patients with NPC.